A validated inherent stability indicating HPTLC method for estimation of cyclobenzaprine hydrochloride in tablets and use of MS-QTOF in characterization of its alkaline stress degradation product - Minal T. Harde; Sagar B. Wankhede; Praveen D. Chaudhari (Faculty of Pharmacy, Cairo University, 2016)
A simple, selective and sensitive stability indicating high-performance thin-layer chromatographic method was developed and validated for estimation of cyclobenzaprine hydrochloride (CBP) in bulk drug and commercial tablets according to ICH guidelines. A precoated silica gel 60F254 HPTLC plates were used for chromatographic separation using mobile phase toluene: ethyl acetate: methanol: glacial acetic acid in the ratio 4:2:3.5:0.5 v/v/v/v. A TLC scanner was set at detection wavelength 290 nm for densitometric analysis of analyte on absorbance mode. The degradants were resolved satisfactorily in a mixture of stressed sample having Rf values 0.48 ± 0.05, 0.52 ± 0.05, 0.86 ± 0.05, 0.66 ± 0.05 and 0.27 ± 0.05. The calibration curve of drug was found linear in the concentration range 200-1000 ng/band. The (r2 > 0.999) correlation coefficient value indicated good correlation between the analyte concentrations and peak areas. The repeatability and intermediate precision study revealed the % RSD value less than 2.0 and was found to be satisfactory. The accuracy of developed method was ascertained by performing the recovery study using standard addition method and expressed by percent recovery (100.32%) which was found satisfactory. CBP was subjected to various stress conditions as per International Conference on Harmonization (ICH) guidelines. The drug showed significant degradation during hydrolytic and oxidative stress condition. CBP remained stable in thermal and photolytic stress testing. The validated chromatographic method was further utilized to isolate the alkaline degradation product using preparative HPTLC technique and extensive FT-IR, ESI-MS/TOF studies were performed to ascertain the structure of degradant.